Plan Colombia’s Onset: Effects on Homicides and Violent Deaths (2014)
In this paper, the link between Plan Colombia and violence is explored. This paper exploits the difference in the success of the program among the different regions to identify the potential side effects on homicides and violent deaths. Results show no significant effects observed on homicides. On the other hand, evidence was found of increases in the number of violent deaths for women living in urban areas, and an opposite negative effect for men living in rural areas. These findings are consistent for different specifications of the model, the cut-off end of the program, and the classification of the regions’ criteria.